Dirasah Tahliliah `An Manhajiah Ta’lif Al-Munjid Li Louis Ma`luf - Istiqomah, Dhia; Ferolisa, Ardhea; Hanan Al Faruqi, Mhd Ibnu; Bahruddin, Uril (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2023)
Al-Munjid is a popular dictionary that contains hundreds or even thousands of vocabulary words, so many people use it even in almost all parts of the world. The aim of this study was to introduce the author to Al-Munjid Dictionary, the method of writing Al-Munjid and the method of revealing words in it, and the advantages and disadvantages of Al-Munjid Dictionary. The method used in this study is qualitative with a library research design. The data collection technique for this research is to search for data, read data, tag data, and list data related to information contained in books, journals, proceedings, print media, and online media. The results of this research: First, Al-Munjid dictionary uses the lexical grouping method that relies on the method of arranging alphabetical patterns. It is included in several forms of dictionaries, and it is also included in several specific lexical objectives. Second: Some scholars believe that Al-Munjid’s dictionary is connected and part of the Orientalist work that concealed the duties and goals of global Islam. Third: Al-Munjid’s dictionary contains five advantages and eight disadvantages.